Triglyceride‐Glucose Index (TyG) is associated with erectile dysfunction: A cross‐sectional study. (19th October 2020) - Yilmaz, Mehmet; Karaaslan, Mustafa; Tonyali, Senol; Celik, Mecit; Toprak, Tuncay; Odabas, Oner
Abstract: Background: Erectile dysfunction (ED) is often associated with endocrine metabolic diseases such as metabolic syndrome (MetS) and diabetes mellitus (DM), in which insulin resistance (IR) plays a decisive role in pathology. Triglyceride‐glucose index (TyG), a simple, inexpensive and easily accessible IR marker, is calculated by fasting serum glucose and triglyceride values. Objectives: We aimed to reveal the relationship between TyG index and ED. Materials and methods: Of 152 male patients, aged between 24‐80 years, admitted to the urology outpatient clinic with complaining erectile insufficiency were evaluated. Liver function tests, complete blood count, fasting serum triglyceride, serum testosterone, fasting glucose, fasting insulin, and hemoglobinA1c (HbA1c) were analyzed. TyG index was calculated. All patients were requested to fill in the validated Turkish version of the 5‐item International Index of Erectile Function (IIEF‐5) survey. Results: A total of 142 patients were included the study. ED was detected in 91 (64.1%) of the patients. BMI, fasting insulin level, fasting glucose level, IR, GGT, HDL, HbA1c, Triglyceride, TyG, DM, HT, and MetS status of the patients in ED group were statistically significantly higher compared to non‐ED group (all P < .05). It was found that the cutoff value of TyG index for ED was 8.88 (AUC = 0.739, sensitivity 67%, specificity = 68.6%). In multivariate logistic regression analysis, age (OR = 1.07, 95% CI = 1026‐1115, P  = .002) and TyG index above 8.88 (OR = 3.865, 95% CI = 1686‐8859, P  = .001) were found as independent predictors of ED after accounting for BMI, serum total T and IR. Conclusion: TyG index might be useful in the diagnosis and follow‐up of ED.